Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Taking flight: An ecological, evolutionary and genomic perspective on bat telomeres - Megan L. Power; Nicole M. Foley; Gareth Jones; Emma C. Teeling (Molecular Ecology, 2022)
Over 20% of all living mammals are bats (order Chiroptera). Bats possess extraordinary adaptations including powered flight, laryngeal echolocation and a unique immune system that enables them to tolerate a diversity of viral infections without presenting clinical disease symptoms. They occupy multiple trophic niches and environments globally. Significant physiological and ecological diversity occurs across the order. Bats also exhibit extreme longevity given their body size with many species showing few signs of ageing. The molecular basis of this extended longevity has recently attracted attention. Telomere maintenance potentially underpins bats’ extended healthspan, although functional studies are still required to validate the causative mechanisms. In this review, we detail the current knowledge on bat telomeres, telomerase expression, and how these relate to ecology, longevity and life‐history strategies. Patterns of telomere shortening and telomerase expression vary across species, and comparative genomic analyses suggest that alternative telomere maintenance mechanisms evolved in the longest‐lived bats. We discuss the unique challenges faced when working with populations of wild bats and highlight ways to advance the field including expanding long‐term monitoring across species that display contrasting life‐histories and occupy different environmental niches. We further review how new high quality, chromosome‐level genome assemblies can enable us to uncover the molecular mechanisms governing telomere dynamics and how phylogenomic analyses can reveal the adaptive significance of telomere maintenance and variation in bats.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Food for folivores: nutritional explanations linking diets to population density - Ian R. Wallis; Melanie J. Edwards; Hannah Windley; Andrew K. Krockenberger; Annika Felton; Megan Quenzer; Joerg U. Ganzhorn; William J. Foley (Oecologia, 2012)